EasyHarvest: App for optimized combine harvester scheduling - CGIAR Research Program on Rice (2019)
A prototype web based application and App (available as Beta version on Playstore) was developed and functionality tested on the IRRI Zeigler Experiment Station with 3 combine harvesters. Currently it is also being tested for digitized logistics of rice straw collection, transportation, and storage in the Philippines.